Environmental analysis of mangrove ecosystems in the southern coast of Purwodadi Subdistrict, Purworejo Regency, Central Java - Setiyaningrum, Ika Feni; Puspitasari, Etika Dyah (Sustinere: Journal of Environment and Sustainability, 2022)
The southern coast of Purwodadi Subdistrict, Purworejo Regency, Central Java, has a mangrove ecosystem which is a part of nature conservation area. Unfortunately, some of the mangrove areas have been converted into ponds by the local community. This study aims to examine the current condition of the mangrove ecosystem, especially following land conversion activities, in terms of physical and biotic aspects. The results of this study can later be used as evaluation material to determine the best approach in sustainably managing the mangrove ecosystem. The method used in this study was the transect line plot for vegetation observation and in situ measurements to obtain physical water data. Aerial photographs were used to determine the area of existing mangroves and the overall state of mangrove vegetation. Data analysis of this study used vegetation index calculations and compared them with the guidelines from the Minister of Environment and Forestry Decree No. 201/2004 and No. 51/2004. This study indicates that the mangrove ecosystem of Purwodadi Subdistrict is in the brackish stream mangroves zone, which is located along with the brackish water flow until the area where the water is almost fresh (barely salty). The dominant vegetations are Rhizophora mucronata and Nypa fruticans. Except for the dissolved oxygen (DO) parameter, the measurement of the physical elements of the waters fulfills the quality criteria. This is due to the presence of shrimp pond waste in the mangrove waters. The salinity level in this area has a value below 10%, unlike the salinity value found in mangrove waters in general.